2023
DOI: 10.3389/fmicb.2023.1179397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arsenic stress on the intestinal structural integrity and intestinal flora abundance of Cyprinus carpio

Abstract: Aquatic organisms such as fish can accumulate high concentrations of arsenic (As), which has toxic effects on fish. However, whether the intestinal flora are involved in As damage to fish intestinal tissues and the underlying process are unclear. Common carp (Cyprinus carpio) were exposed to As (2.83 mg/L) in water for 30 days, and blood, muscle, intestine, and intestine samples were collected. Intestinal pathological sections were observed, and the lipopolysaccharide (LPS) levels in serum and the levels of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Two reports mentioned that Pb exposure damaged chicken muscles [ 25 ] and cerebrums [ 8 ] via morphological observation. Microstructural and ultrastructural observations are morphological observation methods for studying the damage to organisms caused by poisoning [ 26 , 27 , 28 ]. In our experiment, the microstructural observation indicated that excessive Pb caused cerebellar and thalamic injury in chickens, such as smaller and fewer Nissl bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Two reports mentioned that Pb exposure damaged chicken muscles [ 25 ] and cerebrums [ 8 ] via morphological observation. Microstructural and ultrastructural observations are morphological observation methods for studying the damage to organisms caused by poisoning [ 26 , 27 , 28 ]. In our experiment, the microstructural observation indicated that excessive Pb caused cerebellar and thalamic injury in chickens, such as smaller and fewer Nissl bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot is an important method used to explore melecular mechanism of poisoning caused by toxic substances [ 28 , 29 ]. Proteins from the liver extracted from RIPA buffer Protein concentration of each group, were determined by BCA protein assay kit (Beyotime).…”
Section: Methodsmentioning
confidence: 99%
“…The Western blot analysis was performed following established protocols as described in previous studies ( Cui et al, 2023b , Shi et al, 2023 ; Miao et al, 2022 ). Heterophils (2 × 10 5 /well) were stimulated with 80 μM ZEA for 2 h at 37 ° C in a humidified 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%